Plant regeneration of Bauhinia purpurea by tissue culture technique - Saparam, W.; Poeaim, A.; Pongtongkam, P.; Chareonsap, P. P.; Poeaim, S. (My University, 2024)
Results showed that the seed of Bauhinia purpurea germination was archived 100% from half-strength MS medium supplemented with 3.0 mg/L Gibberellic acids (GA3) and gave 71.137 mm for the highest seedling. The optimal condition of nodal explants sterilization was E5, which gave 92% of survival explants. For the shoot induction method, the results showed that 24.270 mm was the highest proliferation of shoots achieved from MS medium supplemented with 1.0 mg/L 6-benzylaminopurine (BAP). The highest number of roots was 2.867 roots, and the highest root length was 33.453 mm, obtained at half-strength MS medium complemented with 0.25 mg/L Indole-3-acetic acid (IAA). The 73.33% of plantlets were survived after being transferred to plastic pot.
Keywords: Bauhinia purpurea; Shoot induction; Sterilization